Clinical outcome and time trends of surgically treated renal cell carcinoma between 1986 and 2010: results from a single centre in Sweden. (4th May 2018) - Grabowska, Beata; Ulvskog, Emma; Carlsson, Jessica; Fiorentino, Michelangelo; Giunchi, Francesca; Lindblad, Per; Sundqvist, Pernilla
Abstract: Objective: The aims of this study were to create a cohort of retrospectively collected renal cell carcinoma (RCC) specimens to be used a basis for prognostic molecular studies, and to investigate the outcome and time trends in patients surgically treated for RCC in a single-centre cohort. Materials and methods: Patients undergoing surgery for RCC between 1986 and 2010 were included in the study. Medical records were reviewed, and the diagnostic tissue was re-evaluated according to a modern classification. The change in patient and tumour characteristics over time was analysed. Results: The study included 345 patients. Smaller tumours, as indicated by primary tumour diameter, tumour (T) stage and American Joint Committee on Cancer (AJCC) stage, were found more frequently in later years compared to the early 1990s. No changes in the clinical outcome for the patients were seen among the time periods investigated. Increasing T stage, AJCC stage, primary tumour diameter and decreasing haemoglobin levels were associated with cancer-specific mortality in univariate analysis. A high calcium level was significantly associated with increased cancer-specific mortality (hazard ratio = 4.25, 95% confidence interval 1.36–13.28) in multivariate analysis. Conclusions: This study on patients who underwent surgery for RCC from 1986 to 2010 at a single institution in Sweden indicates that there has been a change in tumour characteristics of patients diagnosed with RCC over time. It was also shown that calcium levels were an independent prognostic factor for cancer-specific mortality in this cohort. This cohort could provide a valuable basis for further molecular studies.